A support system for civil aviation navigation equipment security management. (March 2020) - Shao, Quan; Jia, Meng; Xu, Chenchen; Feng, Xiaojia
Highlights: A weighted network specifying flow weight and node strength is proposed. Adding new equipment can help balance the node security capacity distribution. The network business continuity is assessed by network topology and network function. Abstract: Civil aviation navigation equipment system has many weaknesses, which easily causes serious problem to air transportation safety. This paper focuses on a support system for civil aviation navigation equipment security management. Firstly, a sustainability assessment platform was constructed to analysis and find out the weaknesses of equipment network. Next, one network expansion planning platform was built to improve the reliability and business continuity of the whole navigation system. Experiments were carried out based on these two platforms. Also, the equipment network of China's eastern part was expanded based on the business continuity assessment. Results proved that the network business continuity and node efficiencies of new equipment network can satisfy the lowest requirement of economic consumption. Finally, the optimal network expansion planning method has been achieved, proving the effectiveness of the civil aviation navigation equipment security management support system.